2018
DOI: 10.1002/jgh3.12072
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for postoperative infection after gastrointestinal surgery among adult patients with inflammatory bowel disease: Findings from a large observational US cohort study

Abstract: Background and AimPostoperative infection (POI) is a major source of morbidity and prolongation of hospitalization in inflammatory bowel disease (IBD) patients. This large observational study was conducted to further describe risk factors and to quantify the proportion of POIs that are preventable.MethodsWe conducted a retrospective cohort analysis of the Optum US health insurance claims database. The study population included adults with ulcerative colitis (UC) or Crohn's disease (CD) who underwent lower gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…Albumin and nutritional status are also essential factors to evaluate during preoperatory management, despite the fact that a higher risk of complications has been observed in those patients with mixed or exclusive parenteral nutrition [ 47 ]. Of note, corticosteroids and hypoalbuminaemia are intimately associated with other factors involved in postoperative complications such as anaemia, the temporality of surgery or the surgical approach [ 48 , 49 , 50 ]. Regarding anaemia, only one study analysed the association between its severity and the risk of complications in IBD [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Albumin and nutritional status are also essential factors to evaluate during preoperatory management, despite the fact that a higher risk of complications has been observed in those patients with mixed or exclusive parenteral nutrition [ 47 ]. Of note, corticosteroids and hypoalbuminaemia are intimately associated with other factors involved in postoperative complications such as anaemia, the temporality of surgery or the surgical approach [ 48 , 49 , 50 ]. Regarding anaemia, only one study analysed the association between its severity and the risk of complications in IBD [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IBD is incurable and increases the risk of lymphoma, cholangiocarcinoma, and colorectal cancer ( Samadder et al, 2019 ; Scharl et al, 2019 ). Many patients with IBD have to undergo surgery multiple times to relieve symptoms, which may lead to postoperative complications and infections, adversely affecting their quality of life ( Torres et al, 2017 ; Ungaro et al, 2017 ; Liang et al, 2018 ). There have been some—although relative few—experiments using immunomodulators for IBD treatment, but the effect of the treatment declines with time ( Torres et al, 2017 ; Ungaro et al, 2017 ; Friedrich et al, 2019 ).…”
Section: Intestinal Inflammationmentioning
confidence: 99%
“…After radical gastrectomy for gastric cancer, post-operative infection is the most common complication via leukocyte depletion in transfusion patient [20]. Postoperative infection is the lethal and hospitalized factor in patients who underwent lower gastrointestinal surgery of the small intestine, colon, rectum, or anus in Unit State [21]. Studies had shown that patients who underwent surgical esophagectomy had a high risk of postoperative complications such as sepsis and high mortality [22].…”
Section: Table 1 Continued: Basic Characteristics Of the Study Particmentioning
confidence: 99%